How Students Learn: Perspective of Medical Graduates about Teaching-Learning and Academic Performance - Supriya Dhakne-Palwe; Sandeep Kadu; Gaurang Baxi; Shrunkhala Kaushik; Mrunal Patil; Madhuri Kanitkar (Healthline, 2025)
Introduction: This study investigates medical students' perceptions of teaching-learning experiences across ten medical colleges affiliated with the Maharashtra University of Health Sciences (MUHS), focusing on high resource colleges (HRCs) and low resource colleges (LRCs). Objectives: To assess the perceived quality of teaching-learning experiences among undergraduate medical students in HRCs and LRCs affiliated with MUHS, and to examine the association between these perceptions, self-reported academic performance, and compliance with teaching schedules. Methods: A cross-sectional study was conducted among 1,024 undergraduate students selected from 10 out of 62 MUHS-affiliated medical colleges, using purposive sampling based on resource availability (5 HRCs, 5 LRCs). Data were collected via a validated 24-item questionnaire administered online. The sampling technique was convenience-based, and the response rate was approximately 14.6%. Statistical analysis included Chi-square tests to compare categorical variables. Results: Statistically significant differences were observed in compliance with planned teaching schedules and perceived quality of education between HRCs and LRCs (p <0.05). HRC students reported higher prevalence of >80% self-reported attendance (53.7%) compared to LRC students (38.1%). Students from HRCs reported higher mean scores for perceived quality of education (4.2 ± 0.5) compared to LRCs (3.5 ± 0.7).  Both groups favoured hybrid learning methods, but LRC students cited infrastructure deficiencies as barriers. Conclusions: The study underscores that resource availability correlates with student perceptions of teaching quality and schedule adherence.